WOMEN's Knowledge of Obstetric Danger signs in Ethiopia (WOMEN's KODE):a systematic review and meta-analysis - Ayele Geleto; Catherine Chojenta; Abdulbasit Musa; Deborah Loxton (Systematic Reviews, 2019)
Abstract Background According to the 2015 World Health Organization report, globally, an estimated 10.7 million mothers died from 1990 to 2015 due to obstetric complications. This report showed that almost all global maternal deaths (99%) occurred in developing countries and two thirds of these deaths took place in sub-Saharan Africa where the majority of women lack knowledge about obstetric danger signs. In Ethiopia, in several research reports, it has been indicated that women have poor knowledge about obstetric danger signs. Although several studies have been conducted to assess women’s knowledge of obstetric danger signs, to date, no systematic review has been conducted in Ethiopia. Therefore, this review is aimed at synthesising the existing literature about women’s knowledge of obstetric danger signs. Methods We systematically searched for articles from MEDLINE, Cumulative Index to Nursing and Allied Health Literature, Embase, Web of Science, Scopus, Google Scholar and Maternity and Infant Care databases. A combination of search terms including ‘knowledge’ or ‘awareness’ or ‘information’ and ‘pregnancy danger signs’ or ‘obstetric danger signs’ or ‘obstetric warning signs’ and ‘Ethiopia’ was used to locate appropriate articles. Two reviewers conducted article screening and data abstraction independently. Observational studies published in English and conducted in Ethiopia to date were assessed for quality using the adapted Newcastle Ottawa Scale for cross-sectional studies. The PRISMA checklist was used to present the findings of this systematic review. Results From the 215 articles initially screened by abstracts and titles, 12 studies fulfilled the inclusion criteria. All the studies reported women’s knowledge of obstetric danger signs during pregnancy, ten articles reported on the level of knowledge during delivery and eight studies reported on the level of knowledge of danger signs during the postpartum period. The pooled random effect meta-analysis level of women’s knowledge about obstetric danger signs during pregnancy, delivery and postpartum was 48%, 43% and 32%, respectively. Maternal age, education, income, health service use, distance from facility and women’s autonomy were reported in several studies as determinants of women’s knowledge of obstetric danger signs. Conclusions Women’s knowledge about obstetric danger signs in Ethiopia was very poor, which could hamper access to obstetric care when women encounter obstetric complications. Counselling services during antenatal care and community-based health information dissemination about obstetric danger signs should be strengthened. Systematic review registration PROSPERO CRD42017077000